Novice middle school teachers’ preparedness for teaching, and the helpfulness of supports: A survey of one state - Chaney, Bradford; Braun, Henry; Jenkins, Frank (Education Policy Analysis Archives, 2020)
Novice teachers’ readiness for teaching may affect the quality of the classroom environment and teachers’ likelihood of remaining in teaching. Using a survey of novice teachers in one state, we examine teachers’ preparedness for teaching, the supports offered, and the perceived helpfulness of those supports. Even novice teachers often had some type of prior experience: particularly substitute teaching (64%) and as a teacher aide or assistant (44%). Still, they often did not feel well prepared. Sixty percent of teachers felt well prepared in their subject area, but only 34% in using appropriate pedagogical strategies, 28% in managing their classrooms, and 17% in reaching all students. Teachers typically received multiple types of supports and received them multiple times over the first year, with a mean of 163 instances of supports. Teachers most often viewed supports as helpful if the supports were in the areas that teachers felt least prepared and provided at least monthly. The supports most related to teachers’ perceptions of helpfulness were mentoring, planning lessons, using student assessment data to make decisions about instruction, using appropriate pedagogical strategies, professional development for new teachers, teacher networks, and regular collaboration with other teachers.